(untitled) (Cambridge, Mass., 1984)
This book should be part of the literature absorbed by policymakers and researchers in the area of input-output research for education. It would serve as an excellent survey text for a graduate course examining the determinants of educational outcomes.
Keywords: Phát triển kinh tế,Economic development; Ảnh hưởng của giáo dục,Effect of education on